2016
DOI: 10.1155/2016/9368483
|View full text |Cite
|
Sign up to set email alerts
|

Danggui Buxue Tang Attenuates Tubulointerstitial Fibrosis via Suppressing NLRP3 Inflammasome in a Rat Model of Unilateral Ureteral Obstruction

Abstract: Inflammation significantly contributes to the progression of chronic kidney disease (CKD). This study aimed to characterize Danggui Buxue Tang (DBT) renoprotection and relationship with NOD-like receptors family pyrin domain-containing 3 (NLRP3) inflammasome expression in rats with unilateral ureteral obstruction (UUO). Sprague-Dawley rats were subjected to UUO and randomly assigned to untreated UUO, enalapril-treated (10 mg/kg/day), and DBT-treated (9 g/kg/day) groups. Sham-operated rats served as controls, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…UUO is recognized as an ideal experimental model of renal interstitial fibrosis. Ureteral obstruction leads to a significant inflammatory and fibrotic response, followed by infiltration of inflammatory cells, renal interstitial myofibroblast proliferation, and ECM accumulation in the renal interstitium (27). We established the UUO model successfully and administered Ad-P311 into UUO rats by the tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…UUO is recognized as an ideal experimental model of renal interstitial fibrosis. Ureteral obstruction leads to a significant inflammatory and fibrotic response, followed by infiltration of inflammatory cells, renal interstitial myofibroblast proliferation, and ECM accumulation in the renal interstitium (27). We established the UUO model successfully and administered Ad-P311 into UUO rats by the tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of these two molecules slows down angiogenesis inside the tumor microenvironment, thus ameliorating tumor progression and distant metastasis. In addition to inhibition of inflammation and angiogenesis in the model of organ fibrosis [36], we further determined that the combined AM and AS therapy can attenuate cancer-related inflammation and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…DGT is an ancient Chinese herbal decoction that has been demonstrated to possess hematopoietic function and has important values in glucose homeostasis, which may be a valid therapy for the control of diabetes and its complications [31]. Besides, protective effects of DGT on renal glomerular mesangium and renal function in STZ-induced rats were also explored [28,32]. Previous report has concluded that DGT could attenuate extracellular matrix components, such as FN or Col IV [9].…”
Section: Discussionmentioning
confidence: 99%